Analisis Implementasi Model Kurikulum Berbasis Eco-Pesantren dalam Membentuk Green Character Santri di Pondok Pesantren Nurul Haramain NWDI Narmada - Ulan Susilawati; Akhmad Syahri; Musta'in Musta'in (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aims to analyze the implementation of an eco-pesantren-based curriculum model in shaping the green character of students at the Nurul Haramain NWDI Narmada Islamic Boarding School. The focus of the study is directed at how ecological values ​​are internalized in the Islamic boarding school education system, although not formalized in a written curriculum, and how this process contributes to the formation of environmentally conscious character in students. This study uses a qualitative approach with a case study type. Data were obtained through in-depth interviews with key informants, participant observation, and documentation, and analyzed using the interactive model of Miles and Huberman which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of eco-pesantren at the Nurul Haramain NWDI Narmada Islamic Boarding School does not take the form of a formal curriculum, but rather is manifested in the daily practices of students through a hidden curriculum mechanism. Ecological values ​​are internalized through habits, role models, and real activities such as independent waste management, environmental cleanliness programs, and reforestation through Green Haramain. This process makes environmental awareness not only cognitive, but also affective and behavioral, thus forming a green character inherent in the students. Furthermore, the Islamic boarding school culture serves as an educational ecosystem that integrates ecological values ​​into all of the students' daily activities in a sustainable manner. The implications of this research indicate that the effectiveness of environmental education does not always depend on the formality of a written curriculum, but rather on the strength of a vibrant and consistent educational culture in daily practice. This culture-based eco-pesantren model can be an alternative approach to contextual ecological character education in Islamic educational institutions, particularly Islamic boarding schools, in responding to the challenges of the global environmental crisis.